CORRELATION BETWEEN PHYSICOCHEMICAL WATER PARAMETERS WITH PLANKTON DIVERSITY - VAISHALI A. MESHRAM; SANYOGITA R. VERMA (The Bioscan, 2025)
Present work was carried out to assess the correlation between water parameters and seasonal variations of plankton diversity of manmade lakes in Anandwan, Warora Dist. Chandrapur (Maharashtra).These lakes were used for irrigation and aquaculture purposes. The water samples were collected from three lakes in the Anandwan regionfrom January 2022 to December 2022. Physicochemical parameters show a positive correlation between temperature and dissolved oxygen. Other parameters viz COD, and BOD are also showing correlation. There exists a significant correlation between the plankton count and the Physico chemical parameter. Total phytoplankton count ranges from 216-5011.2 no/mlbelonging to class Chlorophyceae, Cyanophyceae, Bacillariophyceae, Cryptophyceae, Euglenophyceae, Florideophyceaeand zooplankton ranges from 155-685no/mlfrom Protozoa (paramecium) and Arthropoda phylum viz, Copepods, Cladocera and Rotifera. In Phytoplanktons, out of 12 genera, Closterium was found dominant followed by Cylinderospermum, Fragillaria, and Phacus as well as Batrachospermum. While in Zooplankton Nauplius was reported as dominant followed by Paramecium, Ceriodapnhia dubia, and Branchionus caudatus. Diversity indices, Dominance, and richness index were also calculated.The trend of dominance is as follows: Phytoplankton: Chlophyceae >Cyanophyceae > Bacillariophyceae > Euglenophyceae = Florideophyceae Zooplankton: Copepods > Protozoa > Rotifera> Cladocera